2013
DOI: 10.14233/ajchem.2013.14509
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Nanocomposite Hydrogels and Its in vitro Release Behaviour on Captopril

Abstract: Nanocomposite hydrogels are interesting for biomedical applications due to their bio compatibility and good water sorption diffusion properties. The pH sensitive interpenetrating polymer network based nanocomposite hydrogels was prepared from montmorillonite nanoclays by free radical polymerization and solvent sorption method was used for drug loading. Drug used was captopril an angiotensin converting enzyme inhibitor. Interactions and thermal stabilities were studied using fourier transform infrared spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…It was observed that the pH of the external media and the clay addition order had a profound effect on the swelling characteristics of nanocomposite hydrogels, as shown in Figure 26 . The targeted release of Captopril was observed in the intestine [ 322 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that the pH of the external media and the clay addition order had a profound effect on the swelling characteristics of nanocomposite hydrogels, as shown in Figure 26 . The targeted release of Captopril was observed in the intestine [ 322 ].…”
Section: Resultsmentioning
confidence: 99%
“… Influence of concentration on the cumulative percentage of drug delivery at ( a ) 0.05%, ( b ) 0.1%, and ( c ) 0.15% of capoten-loaded nanocomposite hydrogels. Reproduced with permission from [ 322 ]. …”
Section: Figurementioning
confidence: 99%
“…It was observed that the pH of the external media and the clay addition order had a profound effect on the swelling characteristics of nanocomposite hydrogels, as shown in Figure 26. The targeted release of Captopril was observed in the intestine [322]. Karak et al (2019), highlighted the fundamental concept of nanocomposites of polymers and nanomaterials.…”
Section: Polymer Nanocomposites and Natural Polymeric Carriers In Dru...mentioning
confidence: 90%
“…S. Latha et al (2013) formulated hydrogels of Captopril nanocomposites. Due to their better diffusion, biocompatibility, and excellent water sorption, hydrogels have wide applicability in the biomedical field.…”
Section: Polymer Nanocomposites and Natural Polymeric Carriers In Dru...mentioning
confidence: 99%
“…Saat ini, sediaan transdermal patch banyak digunakan sebagai sistem penghantaran obat dan kosmetik. Sediaan transdermal patch adalah sediaan farmasi non-invasif yang digunakan dengan cara ditempelkan di permukaan kulit yang memungkinkan penyerapan obat melalui kulit dengan keuntungan memberikan konsentrasi obat dalam plasma yang konstan, sehingga dapat meningkatkan bioavailabilitas dan meminimalkan potensi efek samping [4], Komposisi sediaan transdermal patch meliputi bahan aktif, matriks polimer, peningkat permeasi, dan pemlastis. Matriks polimer berfungsi sebagai kerangka dasar patch dan mengatur kecepatan pelepasan obat ke dalam kulit.…”
Section: Abstract: Domperidon Eudragit E100 Eudragit L100-55 Transder...unclassified